2019
DOI: 10.1002/celc.201900228
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Effects of Periodic Polarization on Anodic Electroactive Biofilms

Abstract: Anodic electroactive biofilms (EABs) are commonly grown under continuous polarization of the underlying electrode. Their growth under appropriate periodic polarization was recently reported to considerably enhance their electrochemical properties (catalytic current and charge carriers concentration). This improvement was only investigated on relatively short term (ten days), and its resilience once the periodic polarizations are switched back to continuous (or vice versa) has not yet been assessed. Here, we fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 32 publications
6
23
0
Order By: Relevance
“…Albeit CE and jnormalmnormalanormalx of 1‐CR (149.3±16.3 % and 0.57±0.07 mA cm −2 ) are considerably higher than of 2‐CR (30.2±18.2 % and 0.33±0.14 mA cm −2 ) and 2‐CR+H 2 (49.7±5.2 % and 0.38±0.03 mA cm −2 ) in the 1 st batch cycle, both parameters converge in the following batch cycles to comparable values (Figure b–c). The observed jnormalmnormalanormalx resemble values typically found in literature for Geobacter enrichment biofilms cultivated in 1‐CR and 2‐CR . The derived average CE of 2‐CR (39.7±14.3 %) and 2‐CR+H 2 (48.7±7.7 %) are low compared to the majority of literature.…”
Section: Resultssupporting
confidence: 77%
“…Albeit CE and jnormalmnormalanormalx of 1‐CR (149.3±16.3 % and 0.57±0.07 mA cm −2 ) are considerably higher than of 2‐CR (30.2±18.2 % and 0.33±0.14 mA cm −2 ) and 2‐CR+H 2 (49.7±5.2 % and 0.38±0.03 mA cm −2 ) in the 1 st batch cycle, both parameters converge in the following batch cycles to comparable values (Figure b–c). The observed jnormalmnormalanormalx resemble values typically found in literature for Geobacter enrichment biofilms cultivated in 1‐CR and 2‐CR . The derived average CE of 2‐CR (39.7±14.3 %) and 2‐CR+H 2 (48.7±7.7 %) are low compared to the majority of literature.…”
Section: Resultssupporting
confidence: 77%
“…Although fixed bedBES represent a putative redox stratified environment, [9] their microbial ecology is sparsely investigated. In contrast, EAM and related microbiomes at monolithic electrodes are well studied [28,29] . The redox potential is a key variable to shape microbial composition and microbial physiology including thermodynamics and kinetics of EAM [30–36] .…”
Section: Introductionmentioning
confidence: 99%
“…The EAB in this study was dominated by Geobacter species. Another study by the same group showed that these changes in morphology were only visible when the growing EABs were continuously exposed to these intermittent conditions and for a term longer than 10 days [21]. Regarding electroactive species growing on the anode, no significant effect on the presence of Geobacter was observed.…”
Section: Morphology and Composition Of Eabsmentioning
confidence: 96%
“…In recent years, the interest in the behavior of EABs during intermittent operation has increased [18][19][20][21][22][23]. Kubannek and coworkers measured the CO 2 production as a measure of metabolic activity [24].…”
Section: Figure I Microbial Electrochemical Technologies (Mets) Make Use Of Electroactive Biofilms (Eabs) Thatmentioning
confidence: 99%